Kunstsammlung Nordrhein-Westfalen Düsseldorf : anno 95-96 Jahresbericht. - Essers, Volkmar; Heyden, Thomas; Kruszynski, Anette; Krystof, Doris; Müller, Maria; Müller-Tamm, Pia; Zweite, Armin; Kunstsammlung Nordrhein-Westfalen, Düsseldorf (Düsseldorf : Kunstsammlung Nordrhein-Westfalen, 1997)
Arakawa, Shusaku ; Baertling, Olle ; Beuys, Joseph ; Ernst, Max ; Knoebel, Imi ; Magritte, René ; Morris, Robert ; Richter, Gerhard ; Schultze, Bernard ; Twombly, Cy ; Klee, Paul ; Grosz, George ; Picasso, Pablo ; Schiele, Egon ; Lüpertz, Markus ; Buren, Daniel ; Magritte, René
Biografie
Duits
boek